Voicing Reality : The Hybrid Form of Documentary Music Videos - Hekkens, Roos (My University, 2019)
The documentary music video is an audiovisual expression that adds documentary elements to the music video form. Since its origin, music videos have been a form of experimentation and innovation. Especially in the 21st century the music video form has taken up a broad variety of aesthetics that can be enjoyed online. Moreover, because our reality has become more complex, the audiovisual ways of representing this reality has lead to a wide range of documentary forms. The heterogeneity and flexibility of form allows for documentary elements to integrate with music video characteristics. This study examines how documentary music videos can be defined. Furthermore, it looks at different functions documentary elements can add and how these videos can find a way to give an authentic representation of reality. In addition, this study attempts to understand the meanings that can be created by the synergy between these two divergent audiovisual forms by means of two case studies. The videos selected for this study are “Hidden Wounds” by dEUS and “Wyclef Jean” by Young Thug. These cases are studied through close reading and with focus on the concepts of music video aesthetics, documentary conventions and the potential of hybridity. By looking at the conventions and expectations we have about documentary and music videos, this study tries to understand how these videos voice reality. The study starts by understanding the hybridity of the documentary music video. On the basis of a categorization of the different functions that documentary elements can add, it will become clear how these elements integrate with the music video form. This study introduces amplification, resonation and distortion as functions of the relation between music and image in documentary music videos. The two particular videos that are analyzed are exemplary cases of these different functions. Besides that, the case studies attempt to show the potential documentary music videos have to represent a unique perspective on reality. This study concludes that music videos can be an effective form to give an authentic audiovisual representation of reality and that the documentary elements can functions in versatile ways. Furthermore, it became clear that the connotations we have of music videos as well as documentary are essential in making meaning of documentary music videos. This study recognises the documentary music video as a form of popular culture that voices reality in a meaningful way.
Keywords: Music videos, documentary conventions, hybridity of form, reality